Yeasts and enzymes from vitivinicultural residues for helminthology in agricultural soils - Sosa-Vilca, René Germán (2025)
Vitivinicultural residues represent an abundant source of lignocellulosic biomass which, when transformed by the action of yeasts and enzymes, can modify edaphic conditions and have implications for the ecology of phytoparasitic and free-living nematodes. The objective of the study was to describe yeasts and enzymes from vitivinicultural residues in relation to helminthology in agricultural soils. A descriptive, observational, and exploratory study was conducted between March and June 2025. Twenty-four samples of grape pomace (Vitis vinifera L.) were collected from the “El Campano” winery. The residues were subjected to alkaline and enzymatic hydrolysis, as well as fermentation with yeasts. The presence of fungal species was recorded using conventional microbiological techniques, and the activity of hydrolytic enzymes was determined through qualitative plate assays. A descriptive analysis of frequencies and observed characteristics was applied. The predominant yeast was Saccharomyces cerevisiae (Meyen ex E.C. Hansen, 1883), detected in 75% of the samples, followed by Candida spp. (16.7%) and Hanseniaspora spp. (8.3%). Regarding enzymes, cellulases were detected in 83.3% of the residues, hemicellulases in 62.5%, and pectinases in 50%. The combined action of yeasts and enzymes promoted polysaccharide degradation, increasing the release of soluble compounds with potential effects on edaphic microhabitats. It is concluded that yeasts and enzymes present in vitivinicultural residues constitute relevant ecological factors that can modify agricultural soil conditions and influence the structure and dynamics of phytoparasitic and free-living nematodes, thereby opening new research perspectives in sustainable agroecosystems.